The rhetorical surface of democracy how deliberative ideals undermine democratic politics - Welsh, Scott, 1974-; ebrary, Inc. (Lanham : Lexington Books, 2013)
"The Rhetorical Surface of Democracy: How Deliberative Ideals Undermine Democratic Politics, by Scott Welsh, disputes the idea that democracy has anything to do with public deliberation in pursuit of collective judgment. Welsh argues, rather, that the impossibility of any kind of public judgment is the fact that democracy must face. Given the impossibility of public judgment, rhetorical competitions for political power are not merely poor substitutes for an allegedly more authentic democratic practice but constitute the essence of democracy itself"--
Machine generated contents note: Introduction. The Cure for What Ails You -- Chapter 1. Taking Politics out of Rhetoric -- Chapter 2. Coming to Terms with Rhetoric -- Chapter 3. Democratic Ends -- Chapter 4. Truth Against Judgment -- Chapter 5. Between Rhetorical Reflection and Political Agency -- Conclusion. Democracy at the Edge of the Abyss.
Includes bibliographical references (p. 165-174) and index.
Electronic reproduction.
Keywords: Democracy; Political participation; Rhetoric; Electronic books